2004
DOI: 10.1177/104063870401600519
|View full text |Cite
|
Sign up to set email alerts
|

Eye Infections due toListeria Monocytogenesin Three Cows and One Horse

Abstract: A retrospective study was conducted to determine case histories, microbiological characteristics, and molecular subtypes associated with Listeria monocytogenes infections of the eye in large animals. For selected cases, environmental L. monocytogenes contamination patterns on case farms were also evaluated to probe for potential sources and spread of listerial eye infections. Records of 170 L. monocytogenes isolates from animal infections were reviewed to determine the fraction of isolates associated with eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…Confirmation of REL has been based on the combination of these characteristic histopathological findings associated with immuno-histochemistry (Wilkins et al , 2000; Schwab et al , 2004; Ribeiro et al , 2006; Rissi et al , 2006), bacterial isolation (Yousif et al , 1984; McLaughlin et al , 1993; Johnson et al , 1995), serology (Börkü et al , 2006), and molecular biology (Wiedmann et al , 1997; Evans et al , 2004; Langohr et al , 2006; Bundrant et al , 2011). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirmation of REL has been based on the combination of these characteristic histopathological findings associated with immuno-histochemistry (Wilkins et al , 2000; Schwab et al , 2004; Ribeiro et al , 2006; Rissi et al , 2006), bacterial isolation (Yousif et al , 1984; McLaughlin et al , 1993; Johnson et al , 1995), serology (Börkü et al , 2006), and molecular biology (Wiedmann et al , 1997; Evans et al , 2004; Langohr et al , 2006; Bundrant et al , 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Although molecular investigations have been used worldwide to characterize REL (Wiedmann et al , 1997; Evans et al , 2004; Langohr et al , 2006; Bundrant et al , 2011), reports of the utilization of this diagnostic technique to identify listeriosis in domestic animals from Brazil or South America is scarce. However, REL was successfully characterized in cattle from the state of Paraná by a combination of histopathological and molecular techniques (Headley et al , 2013), and there is one unsuccessful attempt of molecular identification in goats (Rissi et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listerial mastitis is a rare form that usually presents with subclinical chronic interstitial mastitis resulting in parenchymal atrophy (Winter et al 2004). The ocular manifestation of listeriosis is characterised by a granulomatous to purulent keratoconjunctivitis and uveitis/ iridocyclitis (Evans et al 2004;Selbitz 2011). The so-called exposition keratitis is interpreted as a result of cranial nerve paresis and cannot be attributed to the infection itself.…”
Section: Disease Symptoms In Animalsmentioning
confidence: 99%
“…Few cases of encephalitic (Rütten et al 2006), abortive (Welsh 1983), ocular (Evans et al 2004) and septicemic (Jose-Cunilleras and Hinchcliff 2001; Warner et al 2012) forms have been reported. The septicemic form is characterised by necrotizing hepatitis and typhlocolitis.…”
Section: Disease Symptoms In Animalsmentioning
confidence: 99%